Flash-Induced High-Throughput Porous Graphene via Synergistic Photo-Effects for Electromagnetic Interference Shielding - Lee, Jin Soo; Kim, Jeong‑Wook; Lee, Jae Hee; Son, Yong Koo; Kim, Young Bin; Woo, Kyoohee; Lee, Chanhee; Kim, Il‑Doo; Seok, Jae Young; Yu, Jong Won; Park, Jung Hwan; Lee, Keon Jae (Nano-Micro Letters, 2023)
Porous 2D materials with high conductivity and large surface area have been proposed for potential electromagnetic interference (EMI) shielding materials in future mobility and wearable applications to prevent signal noise, transmission inaccuracy, system malfunction, and health hazards. Here, we report on the synthesis of lightweight and flexible flash-induced porous graphene (FPG) with excellent EMI shielding performance. The broad spectrum of pulsed flashlight induces photo-chemical and photo-thermal reactions in polyimide films, forming 5 × 10 cm2-size porous graphene with a hollow pillar structure in a few milliseconds. The resulting material demonstrated low density (0.0354 g cm−3) and outstanding absolute EMI shielding effectiveness of 1.12 × 105 dB cm2 g−1. The FPG was characterized via thorough material analyses, and its mechanical durability and flexibility were confirmed by a bending cycle test. Finally, the FPG was utilized in drone and wearable applications, showing effective EMI shielding performance for internal/external EMI in a drone radar system and reducing the specific absorption rate in the human body. Highlights: 1 Flash-induced porous graphene (FPG) was synthesized via a broad-spectrum flash lamp that induced synergistic photo-effects between ultraviolet and visible-near-infrared wavelengths, resulting in large-area synthesis in just a few milliseconds. 2 A hollow pillar graphene with low sheet resistance of 18 Ω sq−1 was produced, exhibiting low density (0.0354 g cm−3) and outstanding absolute electromagnetic interference shielding effectiveness of 1.12 × 105 dB cm2 g−1. 3 A lightweight, flexible, and high-throughput FPG is applied for electromagnetic interference shielding of a drone radar system and the human body.